Community Satisfaction Index Analysis At Hasanuddin Damrah Manna General Hospital, South Bengkulu District - Sari, Melpa Yupita; Soleh, Ahmad; Nurzam, Nurzam (Social Sciences Journal, 2025)
Health is a basic need for society. This need is what makes people feel the need to maintain their health and obtain health services. Nowadays, people are increasingly aware of the quality of health services that can provide satisfaction to the community itself. In current conditions, hospitals must know how the quality of their services can be received by their consumers, both inpatients and outpatients. Service quality is closely related to customers. The purpose of this research is to determine the analysis of the community / SME satisfaction index at the Hasanuddin Damrah Manna General Hospital, South Bengkulu Regency. The type of research in this research is descriptive using the questionnaire research method. Meanwhile, the data analysis technique used is to measure the value of the Community Satisfaction Index / Smes based on the Regulation of the Minister of State Apparatus Empowerment and Bureaucratic Reform of the Republic of Indonesia Number 14 of 2017 concerning Guidelines for Compiling Community Satisfaction Surveys for Public Service Providing Units which is calculated using the weighted average value each service element.The purpose of this research is to determine the analysis of the community / SME satisfaction index at the Hasanuddin Damrah Manna General Hospital, South Bengkulu Regency. The type of research in this research is descriptive using the questionnaire research method. Meanwhile, the data analysis technique used is to measure the value of the Community Satisfaction Index / SMEs based on the Regulation of the Minister of State Apparatus Empowerment and Bureaucratic Reform of the Republic of Indonesia Number 14 of 2017 concerning Guidelines for Compiling Community Satisfaction Surveys for Public Service Providing Units which is calculated using the weighted average value each service element.